Microbead-based immunoassay using the outer membrane layer of Escherichia coli combined with autodisplayed Z-domains - Kim, Do-Hoon; Bong, Ji-Hong; Yoo, Gu; Chang, Seo-Yoon; Park, Min; Chang, Young Wook; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER, 2016)
The Z-domain has the potential to control the orientation of immobilized antibodies because of its binding affinity to the Fc regions of antibodies (IgGs). In this work, Z-domains were autodisplayed on the outer membrane (OM) of Escherichia coli. OM particles were isolated and coated onto microbeads with positive, neutral, or negative surface charges. Other conditions such as incubation time and initial OM concentration were also optimized for the OM coating to obtain maximum antibody-binding. Using three kinds of model proteins with different isoelectric points (pI), streptavidin (pI = 5, negative charge at pH 7), horseradish peroxidase (pI = 7, neutral charge at pH 7), and avidin (pI = 10, positive charge at pH 7), protein immobilization onto the microbeads was carried out through physical adsorption and electrostatic interactions. Using fluorescently labeled antibodies and fluorescence-activated cell sorting, it was determined that the neutral and the positively charged microbeads effectively bound antibodies while minimizing non-specific protein binding. The OM-coated microbeads with autodisplayed Z-domains were applied to C-reactive protein immunoassay. This immunoassay achieved 5-fold improved sensitivity compared to conventional immunoassay based on physical adsorption of antibodies at the cutoff concentration of medical diagnosis of inflammatory diseases (1000 ng/ml) and cardiovascular diseases (200 ng/ml). (C) 2015 Elsevier B.V. All rights reserved.
Keywords: E. COLI; SPR BIOSENSOR; PARYLENE-N; POLYMERIZATION; COPOLYMER; MECHANISM